Supply Shocks and Real Exchange Rates - Annika Alexius (Sveriges Riksbank, 2000)
Previous studies of the sources of real exchange rate fluctuations have concluded that real demand shocks account for the bulk of the movements in real exchange rates. In this paper, bilateral real exchange rates between the US, the UK, Germany and Japan are investigated using a statistical approach that allows for long-run equilibrium relationships between real exchange rates and the fundamental variables. The results differ from previous findings in that most long run movements in real exchange rates are due to supply shocks. This can be interpreted as empirical support for the Balassa (1964) and Samuelson (1964) relative productivity approach to real exchange rate determination.
Keywords: E50; 330; Real exchange rates; Supply shocks